Eficácia do treinamento de reconhecimento de emoções na qualidade da interação mãe-bebê em mulheres com depressão pós-parto - Renner, Anelise Meurer (2018)
Postpartum Depression (PPD) has a negative effect on newborns and their mothers, and impairments to the mother-infant relationship seem to be harmful to the child’s development. Despite the high prevalence of PPD in Brazil, there are no evaluation protocols and interventions recognized by the country’s unified health service. In order to contribute to an intervention adapted to Brazilian cultural issues and the reality of Brazilian mothers in the postpartum period, two studies were carried out in this dissertation - a theoretical study and an empirical study. The theoretical study aimed to describe two intervention protocols and the respective materials necessary for their execution: a psychoeducation protocol and a training protocol for facial expression recognition. The methodology applied the following steps: (1) state of the art review, (2) preliminary proposal preparation, (3) specialized psychologists’ analysis, (4) pilot study. The study’s resulted in a psychoeducational protocol composed by seven themed primers defining subjects to be addressed with the mothers, in addition to a facial expression training protocol composed by six instruments. The empirical study’s objective was to investigate the effectiveness of both interventions (the psychoeducation and the facial expression training protocol) in the quality of mother-infant interaction. Preliminary results are described in this study, The sample consisted of 14 dyads in which the mothers were diagnosed with PPD by both the EPDS (cut-off point ≥11) and SCID. Dyads were assessed between four and twelve weeks postpartum and were randomized into three conditions: psychoeducation, facial expression training, and waiting list. The results suggested a significant effects of the training groups in maternal ability to recognize anger faces, and a significant effect of the Psychoeducation group on mother-child interaction (proximity and relaxation dimensions). Compared to the waiting list, the two intervention groups produced positive effects, albeit only the Psychoeducation group had an effect on the target primary outcome. Therefore, results suggest that psychoeducation was more effective in increasing the quality of the mother-infant relationship when compared to the other two groups. Further studies with a larger sample size and longer follow-up period are required to investigate these effects further.